Inclusão digital para a Terceira Idade no município de Mãe do Rio - SILVA, Geiziliane Trindade da (2024)
The Digital Inclusion project for the Elderly in the Municipality of Mãe do Rio aims to digitally teach elderly people with little or no experience with computers, promoting digital inclusion for the elderly, providing access and learning to computational resources. The project took place at CRAS (Social Assistance Reference Center). A questionnaire was used as an instrument for data collection. The course had 10 elderly people and a workload of 40 hours, with the syllabus of basic computer skills. The results show that the greatest difficulty encountered by the course participants is related to using the computer caused by eye problems, which is typical of this age group. The reasons that led them to take the course for the majority interviewed was the opportunity to get closer to family and friends, to keep up-to-date and to recover their autonomy. It is concluded that the results of the course were favorable to these people, as they claim that they felt freer and more independent, closer family ties. Through the course it was also found that the elderly have essential skills to acquire new knowledge and that during the course fear and insecurity gave way to autonomy and confidence.